Rola pielęgniarki w profilaktyce i leczeniu odleżyn = The role of the nurse in the prevention and treatment of pressure ulcers - Chrzan, Elżbieta; Chrzan, Paweł; Zukow, Walery; Napierała, Marek; Eksterowicz, Jerzy (Journal of Education, Health and Sport, 2016)
Chrzan Elżbieta, Chrzan Paweł, Zukow Walery, Napierała Marek, Eksterowicz Jerzy. Rola pielęgniarki w profilaktyce i leczeniu odleżyn = The role of the nurse in the prevention and treatment of pressure ulcers. Journal of Education, Health and Sport. 2016;6(12):123-170. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.192461 http://ojs.ukw.edu.pl/index.php/johs/article/view/4041 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 03.12.2016. Rola pielęgniarki w profilaktyce i leczeniu odleżyn The role of the nurse in the prevention and treatment of pressure ulcers Elżbieta Chrzan1, Paweł Chrzan1, Walery Zukow2, Marek Napierała2, Jerzy Eksterowicz2 1Wydział Nauk o Zdrowiu, Radomska Szkoła Wyższa, Radom, Polska 2Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska Słowa kluczowe: rola pielęgniarki, odleżyny, regresja. Key words: the role of nurses, bed sores, regression. Streszczenie Profilaktyka i leczenie odleżyn stanowią niezmiernie istotny problem w opiece pielęgniarskiej. Odleżyny są powodem dodatkowych komplikacji zdrowotnych pacjenta, są źródłem bólu i cierpienia, a także często kłopotów finansowych. Celem niniejszej pracy jest rozpoznanie roli, jaką pełni pielęgniarka w zapobieganiu i leczeniu odleżyn i odpowiedź na postawione pytania problemowe: Problem główny: Jakie znaczenie ma opieka pielęgniarska w profilaktyce i leczeniu odleżyn? Problemy szczegółowe: Jaki zakres czynności prewencyjnych może podjąć pielęgniarka w zakresie zapobiegania odleżynom? Jaką rolę pełni pielęgniarka w leczeniu odleżyn? Czy płeć, wiek i rozpoznanie mają znaczenie w leczeniu odleżyn? Czy długość pobytu pacjenta w szpitalu ma wpływ na postępy w leczeniu odleżyn? Co wnosi standaryzacja profilaktyki przeciwodleżynowej w opiece stacjonarnej? W odpowiedzi na powyższe pytania przyjęłam następujące hipotezy: Hipoteza główna: Pielęgniarka pełni wiodącą rolę w profilaktyce przeciw odleżynowej i leczeniu odleżyn. Hipotezy szczegółowe: Rzetelna na wysokim poziomie opieka pielęgniarska skutecznie zapobiega wystąpieniu u chorych odleżyn. Pielęgniarka ma znaczący wpływ na efekty terapeutyczne w procesie leczenia odleżyn. Wiek, płeć i rozpoznanie u pacjenta są zmiennymi, mającymi istotny wpływ na leczenie odleżyn. Długość hospitalizacji, rozumiana jako czas specjalistycznego, kompleksowego, indywidualnego i wielostronnego leczenia odleżyn, ma korzystny wpływ na postępy w leczeniu odleżyn. Standaryzacja opieki pielęgniarskiej w zakresie profilaktyki i leczenia odleżyn podnosi jakość świadczonych usług medycznych. W pracy zastosowano 3 metody: metodę analizy literatury medycznej oraz metodę analizy dokumentów medycznych, tj. zbiorczej karty profilaktyki odleżynowej, prowadzonej na Oddziale Medycyny Paliatywnej w Szpitalu Specjalistycznym w Puławach w roku 2010. W analizie statystycznej ujęto 124 pacjentów zagrożonych odleżynami. Główną metoda badawcza zastosowano Metodę Wnioskowania statystycznego, model regresji liniowej wielokrotnej. W podsumowaniu końcowym dokonano weryfikacji hipotez. Wszystkie hipotezy są prawdziwe z wyjątkiem hipotezy 3. Wiek i płeć są zmiennymi, które nie mają wpływu na leczenie odleżyn, zaś zmienna rozpoznanie jest statystycznie istotna. We wnioskach końcowych ustalono, że: Pielęgniarki doskonale realizują proces pielęgnowania w zakresie profilaktyki i leczenia odleżyn. Wprowadzenie standardów profilaktyki przeciwodleżynowej przynosi znaczną poprawę jakości świadczonych usług medycznych. Monitorowanie profilaktyki przeciwodleżynowej w postaci rzetelnie prowadzonej dokumentacji zabezpiecza pielęgniarki przed skutkami roszczeń pacjentów. Ogólnie przyjęte zasady leczenia odleżyn przynoszą coraz lepsze wyniki terapeutyczne. Programy profilaktyki i leczenia odleżyn powinny być wdrażane we wszystkich szpitalach, zakładach opiekuńczo-leczniczych i domach opieki. Konieczne jest wprowadzenie kompleksowej edukacji przeciwodleżynowej w środowisku rodzinnym pacjenta, gdyż większość odleżyn powstaje w domu chorego. Świadomość ponoszonych kosztów leczenia odleżyn powinna skłonić menadżerów służby zdrowia do zwiększenia środków finansowych na prewencję odleżyn i ich leczenie według najnowszych osiągnięć nauki. Wyraźnie brakuje w literaturze naukowej pielęgniarskich prac empirycznych z zakresu problematyki i leczenia odleżyn, które pozwoliłyby na weryfikację skuteczności sposobów i metod postępowania w praktyce zawodowej. Summary Prevention and treatment of pressure ulcers are extremely significant problem in nursing care. Bed sores are a source of additional health complications of the patient, are a source of pain and suffering, as well as common financial problems. The purpose of this work is to identify the role played by the nurse in the prevention and treatment of pressure ulcers and the response to the questions of concern: the root Problem: the importance of nursing care in the prevention and treatment of pressure ulcers? Specific problems: what range of preventive activities may take a nurse in preventing pressure ulcers? What is the role of the nurse in the treatment of pressure ulcers? Whether gender, age and diagnosis are important in the treatment of pressure ulcers? Whether the patient's length of stay in hospital has an impact on the progress in the treatment of pressure ulcers? What brings standardization against bed sores stationary care prevention? In response to the above questions it took the following hypothesis: Hypothesis: Nurse full leading role in in prevention against bed sores. and treatment of pressure ulcers. Hypothesis: Sound at a high level of nursing care effectively prevents patients with pressure ulcers. Nurse has a significant impact on therapeutic effects in the process of treatment of pressure ulcers. Age, sex and diagnosis of the patient are variables, which have a significant impact on the treatment of pressure ulcers. Duration of hospitalization, understood as a time of specialized, comprehensive, individual and multilateral treatment of pressure ulcers, has a beneficial effect on progress in the treatment of pressure ulcers. Standardization of nursing care in prevention and treatment of pressure ulcers raises the quality of medical services. In the work uses 3 methods: method medical literature analysis and method of analysis of medical documents. cumulative bed sores prevention card, conducted in palliative medicine in a Hospital Specialized in Puławy in 2010. In the statistical analysis included 124 patients at risk of pressure ulcer. The main test method uses a method of statistical inference, multiple linear regression model. In summary, the final was made the verification of hypotheses. All hypotheses are true except for hypothesis 3. Age and gender are variables, which do not affect the treatment of pressure ulcers, and diagnosis of variable is statistically significant. In the conclusions it was found that: Nurse perfectly carry out the process of nurture in the prevention and treatment of pressure ulcers. The introduction of the standards of prevention against bed sores brings a significant improvement in the quality of medical services. Monitoring the prevention against bed sores in the form of fairly conducted documentation protects nurses against the claims of patients. Generally accepted rules for the treatment of pressure ulcers to bring you more and better therapeutic results. Prevention programs and treatment of pressure ulcers should be implemented in all educational establishments, hospitals and nursing homes. It is necessary to introduce a comprehensive education against bed sores in the family environment of the patient, as most pressure ulcers arise in the House. Awareness of the costs of treatment of pressure ulcers should prompt health care managers to increase financial resources for prevention of pressure ulcers and their treatment according to the latest scientific advances. Clearly missing in the scientific literature of empirical work nursing from the scope of the problems and treatment of pressure ulcers, that would allow for the verification of the effectiveness of ways and practices in professional practice.